Innovations and Support Institutions: the 1st Geographical Indication in Brazil - Yohanna Vieira Juk; Marcos Paulo Fuck (Journal of Technology Management & Innovation, 2015)
The Geographical Indication (GI) is an intellectual property instrument that may allow the adoption of innovations through the appreciation and insertion of origin labeled products in the market. The purpose of this research is to elucidate the role of GI in the specific case of its concession in the Brazilian wine industry. Strategies embraced by producers and a national research institution (Embrapa Uva e Vinho) were aligned to international trends of technological patterns of wine production, noticing the GI as an instrument that could allow the entrance in the wine market as well as could increased the competition. The present analysis aims to prove the validation of this protection mechanism as an instrument that stimulates innovation (productive, organizational or marketing oriented), highlighting the role of support institutions and their possible impacts in the local scope, and also affecting institutional aspects that coordinate the concession of GI in a macro level.